Optimal Strategy for Improving the Quality of Teacher Services through Strengthening Knowledge Management, Interpersonal Communication, Organizational Support and Job Satisfaction - Rusnadi, Sains; Hermawan, Andi; Indrati, Briliantina (Jurnal Penelitian, Pendidikan dan Pengajaran: JPPP, 2024)
Customer perceptions regarding the comparison between fulfilling needs and desires and the accuracy of delivery to balance customer expectations which are closely related to the quality of products, services and human resources are called Service Quality. Teachers are the main aspect and key determinant of successful learning, policy implementation and creative, innovative efforts, as well as the democratization of education. Teachers are the main players and spearheads in the world of education. Therefore, the existence of programs that concretely always support, accompany and help to continue to develop the personal and professional qualities of teachers is a guarantee for brilliant education. Based on preliminary research, it is known that the permanent foundation teachers (GTY) of PGRI Vocational High Schools (SMK) in Bogor Regency have relatively suboptimal service quality. Therefore, research is needed to obtain information on variables related to improving service quality. The aim of this research is to make efforts to improve the quality of service for vocational school teachers by conducting research on the influence of the variables knowledge management, interpersonal communication, organizational support and job satisfaction. This research uses the path analysis method to determine the influence between the variables studied and the SITOREM method for indicator analysis in order to obtain optimal solutions in an effort to improve the quality of vocational school teacher services.